(3MOjK CHj eMeO YGeQ Hf SjGQ GdQbi fRjd MdH Yf TjhNg QMeg Gddgs
(3ChdgG (B:s
(3CNHQfG CHh eMeO GSMGb Hf jMji Hf GSMGb Hf GHQGgje MOKfG CHh eMeO YGeQ Hf SjGQ HMdH SfI GQHY hKdGKjf heGFJjf bGd NQL EdjfG QShd Gddg Udi Gddg Ydjg hSde afgGfG Cf fTQH EdG ai SbGA s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde Ef ef GdTYQ dMceG (B: (3BNQ GdLRA s
(3HBNQgG SeGY SfI (B725 (3hSeGY BNQ HNW GHf MLQ GdYSbdGfi SfI (B805 (3hai CKfGFgG SbWs
(3cJHJ HNW bOje bdjd GdfbWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN SdjeGf Hf UGdM Hf MeO Hf HSGe GdNGUI HYfjRIs
Keywords: (3GdMOjK h GdeUWdMs